Application of dyes as doping agents in MALDI-MS matrices for the signal enhancement of proteins. Issue 11 (20th January 2017) - Ali, Arslan; Shahid, Najia; Musharraf, Syed Ghulam
Abstract : Dyes can significantly influence the ionization of proteins, when used as dopants in conventional matrices used for Matrix Assisted Laser Desorption Ionization Mass Spectrometry (MALDI-MS). Abstract : Matrix Assisted Laser Desorption Ionization Mass Spectrometry (MALDI-MS) is considered as a technique of choice for analysing proteins and peptides. Several modifications have been proposed to increase the sensitivity of MALDI-MS procedure so that low abundant proteins can be targeted. The present work describes the study of the possible increase in MALDI-MS sensitivity by increasing the ion generation via use of dopants in MALDI-MS matrices. These dopant constitutes commonly used dyes such as Coomassie Blue G-250 (A), Cochineal (B), Erythrosin B (C), Sunset yellow (D), and Acid Red 1 (E), which when employed in 0.1–100 pM range along with conventional MALDI-MS matrices such as α-cyano-4-hydroxycinnamic acid (HCCA), sinapic acid (SA) and 2, 5-dihydroxybenzoic acid (DHB), can significantly increase (×2–35) the ion intensity of proteins such as bovine serum albumin (BSA), myoglobin, casein and insulin. Moreover, such effect remains consistent when applied to analyse real samples such as honey and egg white analysis.